(untitled) (African Journal of Public Administration & Management, 2026)
The study examines the programme implementation fidelity and the mutual benefits in the Malawi Government Graduate Internship Programme (GIP). It is premised on the basis that the Malawian Ministry of Labour has been implementing the programme since 2018, reaching out to 13454 young graduates aged 35 and below with the aim of enhancing youth employability. Using a mixed methods approach, the study seeks to determine whether the programme is being implemented as per its design and to examine the value that it brings to both interns and the MDAs that host them. The recommendations from the study will be relevant not only to Malawi’s public service programming with regards to youth employment but also to other African nations seeking to come up with strategies for the same.